Highly efficient single cell arraying by integrating acoustophoretic cell pre-concentration and dielectrophoretic cell trapping. Issue 22 (6th October 2015) - Kim, Soo Hyeon; Antfolk, Maria; Kobayashi, Marina; Kaneda, Shohei; Laurell, Thomas; Fujii, Teruo
Abstract : We present a novel approach for high throughput single cell arraying by integrating two original microfluidic devices: an acoustofluidic chip and an electroactive microwell array. Abstract : To array rare cells at the single-cell level, the volumetric throughput may become a bottleneck in the cell trapping and the subsequent single-cell analysis, since the target cells per definition commonly exist in a large sample volume after purification from the original sample. Here, we present a novel approach for high throughput single cell arraying by integrating two original microfluidic devices: an acoustofluidic chip and an electroactive microwell array. The velocity of the cells is geared down in the acoustofluidic chip while maintaining a high volume flow rate at the inlet of the microsystem, and the cells are subsequently trapped one by one into the microwell array using dielectrophoresis. The integrated system exhibited a 10 times improved sample throughput compared to trapping with the electroactive microwell array chip alone, while maintaining a highly efficient cell recovery above 90%. The results indicate that the serial integration of the acoustophoretic pre-concentration with the dielectrophoretic cell trapping drastically improves the performance of the electroactive microwell array for highly efficient single cell analysis. This simple and effective system for high throughput single cell arraying with further possible integration of additional functions, including cell sorting and downstream analysis after cell trapping, has potential for development to a highly integrated and automated platform for single-cell analysis of rare cells.